PSM staffs triumph at IReX 2024 - Yuhani, Yusof (2024)
IReX 2024 is a prestigious exhibition on 4th Industrial Revolution (IR 4.0) organized by UiTM Kedah on 20-21 May 2024. With participants across the globe like Malaysia, Indonesia and Korea, to name a few and “Innovation Ideas, Transpiring Dreams” theme, this exhibition provides a platform for exchange and networking and fostering collaborations that transcend the borders.